Soft tissues sarcomas of the head and neck: outcome analysis of the Department of Oncological and Reconstructive Surgery, Center of Oncology Maria Skłodowska-Curie Memorial Institute in Gliwice - Krakowczyk, Łukasz; Szymczyk, Cezary; Maciejewski, Adam; Wierzgoń, Janusz; Jędrzejewski, Piotr; Grajek, Maciej; Półtorak, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2009)
Introduction: Soft tissue sarcomas are uncommon malignant neoplasms and constitute less than 1–2% of all cancers. Sarcomas of the head and neck are rare tumours, constituting approximately 10% of all sarcomas. However, the results of new optimal treatment strategies are still disappointing. The optimal treatment for adult head and neck soft tissue sarcomas is surgery with postoperative radiotherapy and/or chemotherapy. Material and methods: We performed an analysis of head and neck sarcomas on 34 patients identified from the Centre of Oncology IMSC in Gliwice between 1993 and 2004 (the age ranged from 29 to 72, average age 49). There were 59% (20 cases) men and 41% women (14 cases). Results: High clinical stage T2 was observed in 90% of the patients. The majority of patients treated by radical surgery resection required reconstruction with free flap. 41% of patients received postoperative radiotherapy. Local recurrence was observed in 35% and distant metastatic in 11%. Five-year overall and relapse-free survival were 68% and 52% respectively. Significant prognostic factors were: tumour grade and stage, margin status and institutional treatment protocol. Conclusions: Tumour size and grade were important prognostic factors affecting survival. Positive surgical margins were significant predictors of poor survival. Surgery is still the mainstay of treatment for most patients with soft tissue sarcomas of the head and neck.